2007
DOI: 10.1002/ajh.21029
|View full text |Cite
|
Sign up to set email alerts
|

Splenectomy for immune thrombocytopenic purpura: Surgery for the 21st century

Abstract: Although immune thrombocytopenic purpura (ITP) is the most common autoimmune hematological disorder, there is still controversy regarding the optimal management of this condition. Medical therapy may cure a proportion of patients with ITP but there are still a significant number of these individuals who are at risk for bleeding events. Surgery has become the least popular therapeutic option for ITP as other medical therapies have become available that attempt to avoid splenectomy and its morbidity. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
1
26
0
2
Order By: Relevance
“…43 We recommend pneumococcal, meningococcal, and Haemophilus influenzae vaccination before splenectomy and periodically every 5 years or according to titers. 1,44 Splenectomy reduces cost. Before TPO-RA, the annual cost of treating severe chronic ITP was estimated to be $40 000, 45 although comprehensive cost-effectiveness studies are lacking in adults.…”
Section: Prosmentioning
confidence: 99%
“…43 We recommend pneumococcal, meningococcal, and Haemophilus influenzae vaccination before splenectomy and periodically every 5 years or according to titers. 1,44 Splenectomy reduces cost. Before TPO-RA, the annual cost of treating severe chronic ITP was estimated to be $40 000, 45 although comprehensive cost-effectiveness studies are lacking in adults.…”
Section: Prosmentioning
confidence: 99%
“…However, increasing numbers of patients are reluctant to undergo splenectomy and physicians are hesitant to recommend it. 9,10 In addition, the risk of overwhelming postsplenectomy infections, although rare, is not predictable and represents a major concern. [11][12][13] Moreover, some authors reported that, despite initial good responses to splenectomy, the risk of late relapse persists during long-term follow-up 14,15 and severe morbidity resulting from surgery is associated with 11% to 30% postoperative complications requiring prolonged hospitalization or readmission.…”
Section: Introductionmentioning
confidence: 99%
“…Some ITP patients who are unresponsive to medical treatment, however, never undergo a splenectomy, perhaps because patients and physicians are reluctant to have a healthy organ removed, and they fear surgical complications like severe bleeding in the setting of low platelet count [3,4]. It is likely that the age or frailty of a patient plays an important role in whether a splenectomy is recommended; thus, patients who ultimately undergo a splenectomy probably represent a selected group.…”
Section: Introductionmentioning
confidence: 99%